2015
DOI: 10.1016/j.jvsc.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hyperperfusion syndrome after endovascular covered stent grafting for a giant extracranial aneurysm of the internal carotid artery

Abstract: Symptomatic giant extracranial internal carotid artery (ICA) aneurysm is a rare and surgically intractable disease. Several authors have described successful treatments for extracranial ICA aneurysm. None, however, have described a perioperative evaluation of cerebral perfusion or a postoperative complication of cerebral hyperperfusion syndrome (CHS). We present a rare case of CHS after endovascular covered stent grafting for a giant extracranial ICA aneurysm. The CHS was successfully managed on the basis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…There have been case reports of CHS without pre-existing significant stenosis in patients undergoing aneurysm coiling [9]. Hirai et al [10] reported a case of CHS after carotid stent grafting for a giant extracranial internal carotid artery aneurysm. They performed spectrophotometric measurements during the procedure and used CT perfusion to monitor the patient's cerebral perfusion status postoperatively.…”
Section: A a B B C C D D E Ementioning
confidence: 99%
“…There have been case reports of CHS without pre-existing significant stenosis in patients undergoing aneurysm coiling [9]. Hirai et al [10] reported a case of CHS after carotid stent grafting for a giant extracranial internal carotid artery aneurysm. They performed spectrophotometric measurements during the procedure and used CT perfusion to monitor the patient's cerebral perfusion status postoperatively.…”
Section: A a B B C C D D E Ementioning
confidence: 99%
“…Cerebral hyperperfusion syndrome (HPS) and remote intracerebral hemorrhage (ICH) after treatment of the large intracranial aneurysm have been noted ( 2 5 ). The mechanism remains unknown, but it was speculated that the alteration of the geometry of the artery might lead to hemodynamic changes of distal arterial trees, which may contribute to cerebral HPS and remote ICH; nonetheless, this speculation has not been well studied ( 2 , 4 , 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first approach is to design NiTi materials that combine the geometrical characteristics of engineering materials with the functional properties of NiTi to offer new and improved performances. Typical examples include NiTi textile and stents [26,27], cellular and honeycomb designs [18,19], and porous microstructures [17]. These materials exhibit shape memory behaviour and superelasticity in a light weight design.…”
Section: Introductionmentioning
confidence: 99%